Business Planning : Come-Bin Trading / Mohd Shahnan Che Jamel ... [et al.] - Che Jamel, Mohd Shahnan; Jusoh, Ahmad Faiz; Ismail, Mohd Samsul; Wan Junoh, Wan Muhammad Fikri; Ab Azib, Mohd Asrull Naim; Mohd Napi, Mohd Nasya Azlief (2009)
COME-BIN TRADING will establish and introduce at Bukit Tiu, Machang, Kelantan on 1st May 2009. We operating our business in nature partnership and each partner are contributing their capital equally which are RM 6520 each. We discover that our main competitors, which are Dusun Jaya Sdn. Bhd, Golden Valley Farm, D’Honest Farm and Osman Goat Farm. We provide the best quality and our product to satisfy the consumer. Our product consists of goat and goat meats sell directly to the customer. Presently, we are providing the special price to our customer market as the promotion price to our targeting customer. Our target customer’s was according to demographic segmentation. Where as, the demographic segmentation we target on customer age 25 year and above and also the people with income above RM 1,500 per month. We decide to separate location of office and farm yard because if the office in our farm yard, consumer is difficult to defined it and when our farm near to the town, it can cause of problems. The distance between office and farm is about 5.2 KM, and not too far. Other than that our farm is near to the suppliers. When office at to, customer can easily negotiate with our promoter. The reason we select this business because to meet the high demand in the market and its increase by the year. Beside that, government support as they mention in RMK 9. Other than that, the reason is to develop the “Halal Hub” and “Halal Food” industries in Malaysia and lastly, we realize the advantages and benefits of goat meat between the others. In our future, we want to expand our business by establish new branch and also can introduce our product to the foreign country as Islamic country